Imaging features of CT and MR in hepatic perivascular epithelioid cell tumor: case series and literature review - Ning Li; Hui Liu; Jing Chen; Yu Kang; Jing Zhou; Janhua Wang (Frontiers in Oncology)
ObjectiveTo retrospectively analyze the clinical and imaging data of 4 patients with hepatic PEComa of different pathological grades, and to review relevant literature, aiming to enhance clinical awareness of this disease and provide support for preoperative diagnosis.MethodsA retrospective analysis was conducted on 4 cases of patients with hepatic PEComa who were confirmed by surgery and biopsy in our hospital. All patients had complete clinical data, including laboratory tests, abdominal imaging studies, as well as pathological and immunohistochemical examinations.ResultsFour cases of hepatic PEComa were identified. All patients were female, aged between 51 and 62 years. The largest diameter of the lesions ranged from 2.4 cm to 20.0 cm. All four lesions presented a round or oval shape with well-defined margins. Three lesions showed homogeneous density/signal, while one lesion displayed heterogeneous density with extensive necrosis. All four cases had a rich blood supply, characterized by significant enhancement in the arterial phase. In two cases, curved and dilated feeding arteries were observed at the periphery of the lesions, and in one case, early visualization of the hepatic vein occurred during the arterial phase. Immunohistochemical staining was positive for HMB45 (+/++), Melan-A (+/++), and SMA (+/++) in all four cases.ConclusionHepatic PEComa is a rare tumor with no typical clinical manifestations, and laboratory tests usually show no significant abnormalities. CT and MRI are valuable in preoperative diagnosis. When a lesion exhibits prominent arterial phase enhancement along with thickened and tortuous vessels, and there are no specific findings in the clinical history and laboratory tests, hepatic PEComa should be included in the differential diagnosis.